2005
DOI: 10.21236/ada433231
|View full text |Cite
|
Sign up to set email alerts
|

Experiments in Transient Growth and Roughness-Induced Bypass Transition

Abstract: SummaryThe work reported here is a series of wind-tunnel experiments that establishes the basic behavior of roughness-induced disturbances that undergo transient algebraic growth in a laminar boundary layer. The experiments explore three aspects of these disturbances' behavior: their fundamental response to various configurations of surface roughness, their receptivity, and their behavior when the surface roughness amplitude is large. The experiments consist of hotwire measurements of the steady and unsteady d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A series of experiments aimed at the understanding of roughness-induced transient growth was conducted by, e.g. White & Ergin (2003), Ergin & White (2005, Denissen & White (2008); the major findings are compiled in White (2005). White & Ergin (2003) observed that the energy associated with transiently amplified disturbances scales with Re 2 kk for roughness elements.…”
Section: Introductionmentioning
confidence: 99%
“…A series of experiments aimed at the understanding of roughness-induced transient growth was conducted by, e.g. White & Ergin (2003), Ergin & White (2005, Denissen & White (2008); the major findings are compiled in White (2005). White & Ergin (2003) observed that the energy associated with transiently amplified disturbances scales with Re 2 kk for roughness elements.…”
Section: Introductionmentioning
confidence: 99%